Stressovye situatsii i metody sniatiia stressa - Andreeva I. A., Ros' A. I. (Psychology of Personal Interaction in Modern Society, 2024)
This article examines the impact of stress on the mental development of a person in various life situations. Special attention is paid to stress relief methods and the formation of an adequate mental behavioral response. The paper describes neurotic and communicative reactions of a person to stressful situations and discusses ways to overcome them. Given the urgency of the problem, the authors highlight the need to develop and apply innovative methods of working with mental reac-tions to stressful situations. Stress relief recommendations include physical exercise, relaxing prac-tices, socializing, and hobbies.
Keywords: стресс; стрессовые ситуации; психологическая помощь; психическое развитие; методы снятия стресса; психические реакции; невротические реакции; коммуникативные реакции; депрессивные проявления